Phytochemicals: Potential Therapeutic Interventions Against Coronavirus-Associated Lung Injury - Majnooni, Mohammad Bagher; Fakhri, Sajad; Shokoohinia, Yalda; Kiyani, Narges; Stage, Katrina; Mohammadi, Pantea; Gravandi, Mohammad Mehdi; Farzaei, Mohammad Hosein; Echeverría, Javier (Frontiers in Pharmacology, 2020)
Since the outbreak of Coronavirus Disease 2019 (COVID-19) in December 2019 was detected, millions of people have been infected and died worldwide. On the other hand, no drug has been approved for the treatment of this disease and its complications, which urge the need for finding novel therapeutic agents to combat. Amongst the most complications in COVID-19, lung injury has attained special attention. Besides, phytochemicals have shown prominent anti-inflammatory effects and thus possess significant effects in reducing lung injury caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). In addition, prevailing evidence are revealing the anti-viral effects of those phytochemicals, including anti-SARS-CoV activity, which could pave the road in providing suitable lead compounds in the treatment of COVID-19. In the present study, candidate phytochemicals and related mechanism of action have been shown in the treatment/protection of lung injuries induced by various methods. In term of pharmacological mechanism, phytochemicals have shown potential inhibitory effects on inflammatory and oxidative pathways/mediators, involved in the pathogenesis of lung injury during COVID-19 infection. Also, a brief overview of phytochemicals with anti-SARS-CoV-2 compounds have been presented